You need to multiply each term in the left bracket by each term by the right bracket and sum them.
*Image attached*
First multiply [tex]x^2[/tex] by the whole second bracket [tex](-2x^2+4x-1)[/tex]:
[tex]x^2*(-2x^2+4x-1)=-2x^4+4x^3-x^2[/tex] and call this equation (1)
Then, similarly;
[tex](-2x)*(-2x^2+4x-1)=4x^3-8x^2+2x[/tex] equation (2)
Finally;
[tex]3*(-2x^2+4x-1)=-6x^2+12x-3[/tex] equation (3)
Then add the results of equation (1) and(2) and(3):
[tex]-2x^4+4x^3-x^2+4x^3-8x^2+2x-6x^2+12x-3=[/tex]
[tex]-2x^4+8x^3-15x^2+14x-3[/tex]
Hope this helps.